Analisis Pendapatan Penerima Bantuan Langsung Masyarakat-Pengembangan Usaha Agribisnis Perdesaan (BLM-PUAP) di Kabupaten Barito Kuala - Andi Suci Anita; Umi Salawati (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
This study aims to determine the general picture of the implementation of the Direct Community Assistence-Rural Agribusiness Development (BLM-PUAP) in the Barito Kuala Regency; Comparison of recipient and non recipient of BLM-PUAP and to analyze the factors affecting income–of recipient of Direct Community Assistance-Rural Agribusiness Development (BLM-PUAP). Research was conducted in Barito Kuala Regency as one of the districts receiving BLM-PUAP in fiscal year 2008 by taking two representatives subdistricts, those are Tabukan and Mandastana. This study uses survey and interview methods directly through the technique of structured interviews (using questionnaires) with 100 respondents (50 BLM-PUAP recipients and 50 non-recipients). The average income of the BLM-PUAP recipient was Rp 6.799.670, while for non-BLM-PUAP recipients was Rp 4.299,939 and there is a difference in income between the recipient and non- recipient of BLMPUAP fund. Income was simultaneously affected by variable amount of BLMPUAP funds, own capital, age, education level, experience, number of family members, and the dummy type of business. Partially, variables of BLM-PUAP Fund, amount of own capital, age, experience,and number of family members covered significantly affected the family income.